VD_FINDINFO HC / 2021 / 797 vom 16. September 2021 - VD Tribunal cantonal (2021)
PROPOSITION DE CONCILIATION, BAIL À LOYER, LOYER INITIAL, OPPOSITION TARDIVE, DOMMAGE IRRÉPARABLE | 143 al. 1 CPC (CH), 148 al. 1 CPC, 211 al. 1 CPC (CH), 211 al. 3 CPC (CH)